(3MOjbI GdRgQ aj YO Bi GdShQs - (3HQgGf GdOjf CHh ESMGb EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdLYHQj,J (B732 (3g` s
(3ChdgG (B:s
(3HOCJ HMeO Gddg Chd ebUOi hUdjJ HYOg Ydi GdWgQ CMeOi s
(3BNQgG (B:s
(3hJe fXGe YO GdBjGJ RGfg eYGf MdJ ai hSW OQ efVOi hdG QH EdG Gddg aGYHOg eNdUkG hUdi Ydi GdgGOi HGdESHGZ hGbJOi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3YOO CHjGJgG (B59 (3HjJs
(3efXheI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B14s
Keywords: (3GdbQGAGJ hGdJLhjOs